Increasing resistant starch content in fish crackers through different cooking temperatures in repetitive cooking-chilling cycles - Mohd Nor, Mohd Zuhair; A. Talib, Rosnita; Mohd Adzahan, Noranizan; Chin, Nyuk Ling; Hashim, Kamaruddin (Faculty of Engineering, Universiti Putra Malaysia, 2012)
This work describes the effect of different cooking temperatures in repetitive cooking-chilling (RCC) process on resistant starch (RS) content in fish crackers prepared from a ratio of 1:1 fish:sago starch formulation. Three sets of 4 RCC cycles were performed on the fish crackers where each set was cooked at a fixed temperature of 100, 115 or 121°C respectively. Meanwhile, the chilling temperature was fixed at 4°C in all cases. Subjecting the fish crackers to higher cooking temperature for up to 4 cycles of RCC increased the RS content; however, some drawbacks on the quality characteristics namely linear expansion and physical attributes of the crackers were observed. Application of higher cooking temperature in the RCC caused more damages (cracks, burst and fragments) to the shape of the fish cracker gels as observed during the first RCC cycle and when the products were subjected to frying, their linear expansion decreased. This work demonstrated that the application of higher cooking temperature up to 4 RCC cycles was able to enhance the RS content in the fish crackers, but was less able to attain higher percentage of product with perfect shape. On the contrary, fish crackers that were exposed to a lower cooking temperature contained lower RS but with less damaged shape.